1996
DOI: 10.1128/mcb.16.8.4327
|View full text |Cite
|
Sign up to set email alerts
|

Repression of p27kip1 Synthesis by Platelet-Derived Growth Factor in BALB/c 3T3 Cells

Abstract: We have investigated the regulation of p27 kip1 , a cyclin-dependent kinase inhibitor, in BALB/c 3T3 cells during growth factor-stimulated transition from quiescence (G 0 ) to a proliferative (G 1 ) state. The level of p27 kip1 protein falls dramatically after mitogenic stimulation and is accompanied by a decrease in cyclin E associated p27 kip1, as well as a transient increase in cyclin D1-associated p27 kip1 that later declines concomitantly with the loss of total p27 kip1 . Analysis of metabolically labelle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
136
1
1

Year Published

1998
1998
2008
2008

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 160 publications
(141 citation statements)
references
References 70 publications
3
136
1
1
Order By: Relevance
“…The abundance of p27 is thought to be regulated by translational and post-translational pathways, and less commonly at the level of transcription (Agrawal et al, 1996;Hengst and Reed, 1996;Roberts et al, 1994;Vlach et al, 1997). Our own observation suggests that the in vivo proteolysis of p27 by a CPP32-like caspase during early G 1 arrest could be an additional posttranslational regulation pathway of p27.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…The abundance of p27 is thought to be regulated by translational and post-translational pathways, and less commonly at the level of transcription (Agrawal et al, 1996;Hengst and Reed, 1996;Roberts et al, 1994;Vlach et al, 1997). Our own observation suggests that the in vivo proteolysis of p27 by a CPP32-like caspase during early G 1 arrest could be an additional posttranslational regulation pathway of p27.…”
Section: Discussionmentioning
confidence: 74%
“…It is generally up-regulated in cells arrested either by cell contact, serum deprivation or after incubation with transforming growth factor-b (TGF-b) Polyak et al, 1994a;Slingerland et al, 1994). In contrast, p27 usually declines in the presence of mitogenic agents like platelet-derived growth factor, macrophage stimulating factor or interleukin-2 (Agrawal et al, 1996;Kato et al, 1994;Nourse et al, 1994). Nevertheless, recent data obtained with p27 nullizygote mice have shown that cell cycle arrest induced by TGF-b, rapamycin or contact inhibition remains una ected (Nakayama et al, 1996), suggesting that p27 is not the only CKI involved in cell growth arrest under these conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Autoradiographic ®lm was purchased from Kodak (Rochester, NY, USA). Antibodies utilized in this study were anti-cyclin A, a kind gift from Ed Leof (Mayo Clinic), and anti-Kip (Agrawal et al, 1996).…”
Section: Chemicals and Reagentsmentioning
confidence: 99%
“…Cyclin B binds and activates cdc2, forming a complex that is essential for triggering the onset and passage through mitosis. The regulation of the cyclin proteins appears, for the most part, to be periodic, and is con®ned to the interval in which the corresponding activities are required, although there are exceptions such as cyclin E and cyclin D3 (Agrawal et al, 1995(Agrawal et al, , 1996, which are present even in quiescent cells. In addition to the regulatory roles of cyclins on cdk activity, another class of proteins, cyclin dependent kinase inhibitors (CKI), have been described to provide negative control under conditions where the proliferative response must be attenuated, such as density arrest and in response to DNA damaging agents.…”
Section: Introductionmentioning
confidence: 99%
“…p27 is constitutively expressed in many cells, and the level of this protein is elevated in G0 phase and declines as cells in culture enter the cell cycle (Poon et al, 1995;Agrawal et al, 1996;Polyak et al, 1994). p27 may play an important role in governing the growth factor restriction point by ensuring that CDK activity is suppressed during G0 and early G1 phase (Coats et al, 1996;Soos et al, 1996).…”
Section: Introductionmentioning
confidence: 99%